1983
DOI: 10.1051/rnd:19830213
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in premature mice at birth and during neonatal development

Abstract: Summary. This paper reports a statistical study of mortality and the number of newborns per litter. Two types of mortality were observed in premature mice, mortality at reanimation and breeding mortality. Mortality at reanimation was about 13 % ; breeding mortality, occurring only during the first 3 neonatal days, was of two types : primary neonatal mortality (10.9 %), occurring from the end of reanimation up to 6 h after birth, and secondary neonatal mortality (6.9 %) which appeared from days 2 to 3. The ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…But the clustering result indicates that the expression profile of E18.5 is more similar to those of time points after birth. It was reported that premature mice by caesarean section could not live if their gestational ages were less than 19 days [5]. While caesarean birth mice can survive and their weight handicaps in organs can be overcome in postnatal days [6].…”
Section: Resultsmentioning
confidence: 99%
“…But the clustering result indicates that the expression profile of E18.5 is more similar to those of time points after birth. It was reported that premature mice by caesarean section could not live if their gestational ages were less than 19 days [5]. While caesarean birth mice can survive and their weight handicaps in organs can be overcome in postnatal days [6].…”
Section: Resultsmentioning
confidence: 99%
“…To benefit maternal or fetal health, preterm cesarean delivery may be performed after either medically indicated or spontaneous preterm labor. To investigate the effect of cesarean delivery on fetal development and mortality, researchers surgically removed mouse fetuses before the normal delivery date and found that pups of the strain CD-1 could only be resuscitated when delivered on 19 or 20 dpc (20 dpc was the normal delivery time for this strain in their colony) [65], indicating that mice cannot survive outside the uterus if birth occurs more than 1 day preterm.…”
Section: Mouse Models Of Preterm Birthmentioning
confidence: 99%
“…As the mortality of prematures has been studied carefully in primates, domestic animals and rodents (Loctin and Delost, 1983a) (Loctin, 1980 (Loctin, 1980 ;Loctin and Delost, 1983a (Loctin and Delost, 1983a) (Loctin, 1980 (Loctin, 1980) ; (2) there is a high loss of water and sodium in the first 6 neonatal hours in premature mice due to kidney immaturity (Loctin and Delost, 1982). Thus, omitting the weight of stomach milk, the body weight of full-term newborns increased by 2.5 % between birth and 6 h, whereas that of premature mice decreased by 4 %.…”
Section: Introductionmentioning
confidence: 99%